Evaluasi Program Pelatihan Pola Pikir Al-Qur’an di Kampus Kahfi Bagus Bina Cendekia (BBC) Motivator School - Syarifah Hidayahna; Nabilah; Ahmad Fauzi (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
The KAHFI Bagus Bina Cendekia (BBC) Motivator School campus is a non-formal educational institution that conducts a Qur'anic mindset training process to improve the social skills of its students. The KAHFI Campus has now graduated many students to become qualified Islamic motivators. However, the Qur'anic mindset training program still needs to be evaluated, so that its contribution to the self-development of students, and campus development in general, can be known. Therefore, it is important to conduct research on the evaluation of the Qur'anic mindset training program.The purpose of this study is to analyze: 1) the context of the Qur'anic mindset training program, 2) the input of the Qur'anic mindset training program, 3) the process of Qur'anic mindset training, 4) the results of the Qur'anic mindset training program. The research approach used is qualitative with descriptive method. The research informants consisted of 4 teachers or trainers and 13 teenage students (20-21 years old). The information retrieval technique used purposive sampling. The evaluation model used is CIPP, which is an evaluation model to measure the effectiveness of training programs, which is seen from the aspects of context, input, process, and product developed by Stufflebeam (1960).The results of this study show: (1) the training context has met the requirements, namely the high interest of students to follow and join the training, (2) training input, that the training curriculum is relevant to the needs and objectives, (3) the training process regarding training media and methods is sufficient to support the implementation of training. However, the implementation of the training has not been fully implemented according to schedule, (4) training results, the quality of graduates is in accordance with the target. Regarding the quantity of participants, it still needs to be increased to meet the target of graduates. The campus has conducted monitoring and evaluation of students continuously on attitudes, knowledge, and skills.